NKB signaling in the posterodorsal medial amygdala stimulates gonadotropin release in a kisspeptin-independent manner in female mice - Fergani, Chrysanthi; Leon, Silvia; Padilla, Stephanie L; Verstegen, Anne MJ; Palmiter, Richard D; Navarro, Victor M (eLife, 2018)
Neurokinin B (NKB) signaling is critical for reproduction in all studied species. The existing consensus is that NKB induces GnRH release via kisspeptin (Kiss1) stimulation in the arcuate nucleus. However, the stimulatory action of NKB is dependent on circulating estrogen (E2) levels, without which, NKB inhibits luteinizing hormone (LH) release. Importantly, the evidence supporting the kisspeptin-dependent role of NKB, derives from models of persistent hypogonadal state [e.g. Kiss1r knock-out (KO) mice], with reduced E2 levels. Here, we demonstrate that in the presence of E2, NKB signaling induces LH release in a kisspeptin-independent manner through the activation of NK3R (NKB receptor) neurons in the posterodorsal medial amygdala (MePD). Importantly, we show that chemogenetic activation of MePD Kiss1 neurons induces LH release, however, the stimulatory action of NKB in this area is Kiss1 neuron-independent. These results document the existence of two independent neuronal circuitries within the MePD that regulate reproductive function in females. Editorial note: This article has been through an editorial process in which the authors decide how to respond to the issues raised during peer review. The Reviewing Editor's assessment is that all the issues have been addressed (see decision letter).
Keywords: reproduction; amygdala; kisspeptin; neurokinin B; neuroendocrinology; estradiol